Gender and Embodiment in the Contemporary Montreal Swing Dance Community - Batty, Megan (Université McGill, 2020)
"This thesis explores embodiment and gender within the contemporary Montreal swing dance community. Drawing on scholarship in musicology, dance studies, jazz studies, and gender studies, I investigate the relationship between dancers and musicians/DJs. I explore the many facets of this choreomusical conversation and trace this dialogic and collaborative relationship on the social dance floor. The contemporary community is a product of the swing revival and navigating issues of authenticity thus becomes an important consideration for dancers, musicians, and DJs alike. One product of this revival is the set of heteronormative values that underpin the contemporary community. I investigate to what extent these values are reified, challenged, or altogether subverted by participants through musical and choreomusical choices. To this end I conducted interviews with six informants, each of whom has experience as both a dancer and musician and/or DJ. Their privileged position arising from their dual experience affords them insight on the ways in which dancers and musicians/DJs function within the community. This thesis builds on existing scholarship by situating the voices of individuals with choreomusical experience in dialogue with existing scholarship, and ultimately revalues the importance of both embodied knowledge and gender within the swing community"– Author's abstract

Représentations du féminin et énonciation lyrique dans la chanson québécoise contemporaine : perspectives sur le sexe/genre chez Ariane Moffatt, Pierre Lapointe et Philémon Cimon - Konaté, Khady (Université d'Ottawa, 2020)
Cette thèse se propose de faire une analyse du discours sur les représentations du féminin et les implications du sexe/genre dans la chanson québécoise contemporaine, à travers les œuvres et la persona de trois auteur·ice·s-compositeur·ice·s-interprètes (ACI): Ariane Moffatt, Pierre Lapointe et Philémon Cimon. Notre analyse part d’abord du constat que les chansons de Moffatt, Lapointe et Cimon figurent des sujets lyriques, dont la parole et le geste sont modulés par les enjeux énonciatifs que posent le lyrisme. Pour rendre compte de la spécificité de la chanson comme pratique poétique réunissant paroles, musique et interprétation, nous proposons de faire une étude sémantique des chansons pour chacun·e des ACI, en nous attardant dans un premier temps aux questions soulevées par le lyrisme, puis en faisant la somme des aspects relevant du sexe/genre présents dans leurs univers sonores respectifs avec le renfort de la théorie féministe et des études de genre, d’après une perspective postmoderne. Notre lecture cherche à souligner les reconduites et les poncifs liés au féminin, mais également à saisir les propositions et les configurations qui s’écartent des lieux communs, tant pour les modèles féminins valorisés que pour les modèles amoureux et les rapports sociaux de sexe et de genre suggérés par les chansons. La comparaison entre les chansons des trois artistes permet ainsi de dégager des points de convergence, tout en révélant les particularités de leurs œuvres.

Imaginary Women, Imaginary Audience: Gender and Top 40 Radio in Montréal - Maki, Christine (Women in Radio: Unfiltered Voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audi ence. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit wom en’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.

Shekhinah in the Music Videos of Leonard Cohen - Měsíc, Jiří (From Page to Screen: Modification and Misrepresentation of Female Characters in Audiovisual Media, 2020)